Improvement Future Candidate of Teachers’ Abilities To Assist Students With Hearing Impairment In The Classroom - Winarsih, Murni; Mursita, Rohmah Ageng (Angstrom Centre of Education, 2024)
Study to equip future educators with the necessary skills and tactics to proficiently assist children with hearing impairments in educational settings. This study holds significant importance for institutions that provide training for teachers, educators specializing in special needs, and policymakers in the field of education. The focus is on promoting effective communication with students who have hearing impairments, highlighting the significance of utilizing assistive devices such as hearing aids and cochlear implants. Curriculum modifications are crucial to ensuring we can obtain educational resources. The study uses academic literature and practical instances to uncover efficacious approaches that instructors can embrace. The results indicate that by employing suitable strategies, utilizing technology, and making necessary modifications to the curriculum, teachers can improve the educational experience and academic achievement of students with hearing impairments. Teachers must possess the necessary knowledge to properly teach, with a focus on teaching tactics, assistive technologies, and curricular changes.